2011
DOI: 10.1093/hmg/ddr162
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype mining in CNV carriers from a population cohort †

Abstract: Phenotype mining is a novel approach for elucidating the genetic basis of complex phenotypic variation. It involves a search of rich phenotype databases for measures correlated with genetic variation, as identified in genome-wide genotyping or sequencing studies. An initial implementation of phenotype mining in a prospective unselected population cohort, the Northern Finland 1966 Birth Cohort (NFBC1966), identifies neurodevelopment-related traits-intellectual deficits, poor school performance and hearing abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 58 publications
5
16
0
Order By: Relevance
“…We propose that phenotypic traits other than schizophrenia have prevented carriers of the 22q11.2 deletion to be included in the control cohorts of these different studies. In contrast, a recent CNV-study of a Finnish birth cohort, comprising ϳ 5,000 genotyped, unselected individuals [Pietiläinen et al, 2011], revealed one 22q11.2 deletion carrier, which is in line with current incidence estimates. This, and other CNVs that are associated with a wide variety of phenotypes, remain present in the population because they repeatedly occur de novo, and because the phenotype is not necessarily incompatible with normal fecundity.…”
Section: Odds Ratios and Penetrance Estimates Of Cnvs With Pleiotropisupporting
confidence: 83%
See 1 more Smart Citation
“…We propose that phenotypic traits other than schizophrenia have prevented carriers of the 22q11.2 deletion to be included in the control cohorts of these different studies. In contrast, a recent CNV-study of a Finnish birth cohort, comprising ϳ 5,000 genotyped, unselected individuals [Pietiläinen et al, 2011], revealed one 22q11.2 deletion carrier, which is in line with current incidence estimates. This, and other CNVs that are associated with a wide variety of phenotypes, remain present in the population because they repeatedly occur de novo, and because the phenotype is not necessarily incompatible with normal fecundity.…”
Section: Odds Ratios and Penetrance Estimates Of Cnvs With Pleiotropisupporting
confidence: 83%
“…This so-called phenotype mining was performed in an initial study by Pietiläinen et al [2011], based on an unselected, well-described population cohort from Northern Finland, demonstrating the potential applications of this method. They show that individuals with deletions 1 500 kb are more likely to exhibit specific brain-related traits, such as IQ !…”
Section: Technological Advances In the Genetic Diagnosis Of Brain-relmentioning
confidence: 99%
“…We analyzed the relationship between the 4q12 and 22q11.22 deletions and seven neurodevelopmental phenotypes evaluated previously with respect to large deletions in 4,872 genotyped members of the Northern Finland 1966 Birth Cohort (NFBC1966) 10 , a geographically representative population cohort, drawn from the Northeastern sub-isolates as well as the surrounding, less genetically isolated regions; we excluded 59 individuals diagnosed with schizophrenia who were included in the schizophrenia case-control analyses. As with the larger deletions investigated previously in NFBC1966 10 , carriers of the 22q11.22 deletion showed significantly higher frequencies of intellectual deficit compared to non-carriers (OR = 4.6, 95%-CI: 1.41-14.96, p = 0.03), and an even greater overrepresentation of milder learning difficulties (OR= 5.9, 95%-CI: 1.78-8.94, p=0.003) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Considerable evidence supports the association of large deletions, both overall variant burden as well as specific variants, with a wide range of neurodevelopmental disorders, including schizophrenia and cognitive impairment 8, 9 . We previously showed an association between the burden of large deletions and neurodevelopmental phenotypes in a Northern Finnish population cohort, and established that several of these deletions represent founder mutations, carried on haplotypes shared identical by descent 10 . We hypothesized that some smaller deletions might be sufficiently increased in frequency in Northern Finland to enable the detection, by analyses of single-variants, using currently available study samples, of associations to schizophrenia and other neurodevelopmental phenotypes that are particularly frequent in this region.…”
Section: Introductionmentioning
confidence: 95%
“…1,2 CNVs can be either common or rare, and they may account for disease susceptibility and population diversity. 3,4 The frequencies of common CNVs vary across human populations, and in some cases these variants can influence adaptation processes and exposure to natural selection. 5,6 In 2009, Zhao et al 7 analyzed two high-frequency CNVs, which were located on chromosome 22q11.23.…”
Section: Introductionmentioning
confidence: 99%